دراسة طاقة تحمل اطراف الأقواس المشيدة من الخشب البلاستيكي على البقاء مستمرة لأزمنة مختلفة - عباس رولا عبد الخضر (Al-Nahrain Journal of Science, 2012)
In this study an attempt capitalize on wood industry residues in Iraqi architecture after particle wood production in the construction of halls in engineering arches due to environment absence of good timber species. On the subject attended of particles thermosetting wood consists of unsaturated of polyester reinforced of beech wood shell particles again say wood shell particles once, and the (gam) wood shell particles again of particles size ranging between (63-32) were added to each species of particle wood construction (Gypsum) with improving the quality of processed (magnesium oxide and titanium oxide paint). On the study of their characteristics on the problem of flexural creep under four – point loading on horizontal acre from constructions and its effect on bending the pins resist change under load for a long time. the study found results are obvious and clear is that improved energy absorbing polyester material and increased durability for lap add articles mentioned armed with the aim of improving flexural creep modulus. If flexural creep constraints generally are using resin with material reinforcement. Our studies have shown that increasing the ratio reinforcement material from 29 to 36% Turn the flexural creep can multiply modulus thus increasing resistance levels to bend polyester material parties during length download pregnancy also increasing four-point loading from 36.78 to 58.86kPa to enact the damage these parties and the terrible impact of this damage mechanics to increase loss in flexural creep modulus.